PERBANDINGAN MODEL STRUKTUR MENGGUNAKAN METODE MATRIKS DENGAN PROGRAM SAP 2000 - Subaidillah Fansuri; Dwi Deshariyanto; Anita Intan Nura Diana (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
Technological developments in the field of civil engineering have been increasing. One example is the use of computer programs in structural analysis. With this program, engineers often use the program a lot compared to manually. This of course causes the use of manual methods to be increasingly abandoned. Several methods can be used in analyzing the structure, either manual method or by using a computer program. These methods have different paths in analyzing the structure. Based on these differences, a comparative analysis was carried out between the manual method (Matrix Method) and computer program (SAP 2000 Program) related to the calculation results obtained from each method. The object of study analyzed is the Structural Model. The analytical method used is the comparative analysis method. This analysis is related to the comparison of the two methods, namely the Matrix Method and the Sap 2000 Program related to the results of the calculation of the internal forces that will be compared the magnitude and difference and the level of the resulting magnitude. The results of the analysis show that the values generated in the two methods of structural analysis are not the same. Comparison of the results of the structural analysis of the two methods on each rod has a different value difference. Based on the frequency value, each force in the structural analysis has a different level of magnitude. In all structural models of each rod there is a large difference and there is a small difference.